2011
DOI: 10.1167/iovs.10-6612
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Reproducibility of Retinal Thickness Measurements in Two Spectral-Domain Optical Coherence Tomography Machines

Abstract: Considerable differences were found between the two systems, both of which incorporate the spectral-domain technology. Different positioning of segmentation lines, control of localization, density of included scan lines, and number of available maps explain the differences in segmentation quality and reproducibility. Manual correction of segmentation and centralization improves the reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 22 publications
0
47
0
2
Order By: Relevance
“…Krebs et al also reported greater retinal thickness with the Spectralis instrument (370.9 ± 105.4 µm) compared with the Cirrus instrument (271 ± 87.3 µm) in wet AMD patients. 13 In this study, the posterior line was positioned along Bruch's membrane in 84.4% of PED patients. Moreover, in 44.4% of those cases, identification of the posterior boundary failed, following partially both Bruch's membrane and RPE.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Krebs et al also reported greater retinal thickness with the Spectralis instrument (370.9 ± 105.4 µm) compared with the Cirrus instrument (271 ± 87.3 µm) in wet AMD patients. 13 In this study, the posterior line was positioned along Bruch's membrane in 84.4% of PED patients. Moreover, in 44.4% of those cases, identification of the posterior boundary failed, following partially both Bruch's membrane and RPE.…”
Section: Discussionmentioning
confidence: 88%
“…The Spectralis OCT typically segmented the back edge of the same hyper-reflective band, leading to somewhat thicker retinal thickness measurements. 13 However, the Spectralis algorithm failed to properly segment the central B-scan in 25 eyes (92.6%). In 20 of these eyes, the algorithm followed Bruch's membrane instead of the RPE (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations